ANALISIS FAKTOR TRUST DAN PENGARUH TRUST TERHADAP LOYALTY NASABAH INTERNET BANKING - ENTOT SUHARTONO NUR ANISSA (Jurnal Ilmiah Infokam, 2014)
Internet Banking is one of the strategies used by the banking industry to be competitive. Internet Banking is a major concern and a revolutionary strategic weapon bank operations, for delivery or to download the competition between banks. There is a trend change in the attitude of customers because of certain factors, where there are some customers who are reluctant to use internet banking because of these factors, so that the change in the customer's intention to use the service. This study aims to determine the factors that affect the trust and whether the trust affect user loyalty in internet banking customers in the city of Semarang. Data analysis was performed using multivariate techniques Structural Equation Model ( SEM ) and as a tool, this study uses LISREL software. Based on the results of the study showed that the shared values ​​significantly influence user trust, communication between the users of internet banking with a significant effect on user confidence, control of the bank committed fraud against the possibility of Internet banking users no significant effect on user trust, the trust users have a significant effect on user loyalty to using internet banking. Keywords: Trust, Loyalty, Internet Banking